Exploring expressed concerns and uncanny feeling in patients with shortness of breath calling out-of-hours primary care - Michelle Spek; Dorien L. Zwart; Esther de Groot; Michelle R. Timmerman; Maarten van Smeden; Daphne C. A. Erkelens; Anna S. M. Dobbe; Mathé Delissen; Frans H. Rutten; Roderick P. Venekamp (BMC Primary Care)
Abstract Background Patients contacting out-of-hours primary care (OHS-PC) with shortness of breath (SOB) are often concerned. Sometimes, they also have an uncanny feeling; existential anxiety that something is wrong in their body. How concerns and uncanny feeling are related to critical medical conditions that cause SOB is unknown. We therefore explored the relation between expressed concerns and researcher’s judged uncanny feeling among patients who contact OHS-PC for SOB with potential life-threatening events (LTEs) as the outcome. Methods This is an explorative cross-sectional study. We analysed telephone triage conversations from patients with SOB who contacted Dutch OHS-PC between September 2020 and August 2021. We recorded whether patients expressed concerns and we judged whether patients had an uncanny feeling. We calculated odds ratios (ORs) for the association between (i) expressed concerns and (ii) uncanny feeling with the outcome potential LTEs. Results Of the 1,843 patients with SOB, 43.6% patients expressed concerns and 33.0% had an uncanny feeling. Potential LTEs were similarly present among those who did and did not express concerns (OR: 1.07; 95% CI 0.84–1.37, mOR: 1.07; 95% CI 0.83–1.36), whereas potential LTEs were more often present among those with an uncanny feeling compared to those without such feeling (OR: 1.36; 95% CI 1.06–1.75, mOR: 1.35; 95% CI 1.05–1.74). Conclusions Among patients who contacted OHS-PC with SOB, a perceived uncanny feeling of the patient was associated with a higher odd of potential LTEs, while patient’s expressed concerns were not. Critical reflective interpretation is needed as uncanny feelings are difficult to judge. Nevertheless, our results implicate that further research into uncanny feelings in telephone triage could further improve the understanding of the relation with potential LTEs. Furthermore, this could be used to investigate how triage nurses may become more sensitive to what the patient is feeling but not explicitly saying such as by paying special attention to paralanguage. Trial registration The Netherlands Trial Register, number: NL9682, registration date: 20–08-2021.